Rationalizing blood transfusion in cardiac surgery: the impact of a red cell volume-based guideline on blood usage and clinical outcome. - Slight, R; O'Donohoe, P; Fung, A; Alonzi, C; McClelland, D; Mankad, P (2008)
BACKGROUND AND OBJECTIVES: Cardiac surgery is currently considered one of the heaviest users of red blood cells. An explanation may be found, in part, in considering the effect of the heavy clear fluid load associated with cardiopulmonary bypass. This may result in the artificial depression of haemoglobin concentration, overestimating the requirement for red cell transfusion if this is the sole parameter considered. To address this issue, we examined the impact of a red cell volume-based transfusion guideline on transfusion requirement. MATERIALS AND METHODS: This was a single-centre, randomized controlled trial. The cohort of 86 patients was allocated to receive red cells as per the red cell volume guideline (group RCV) or standard haemoglobin concentration-based departmental policy (group C). Outcome measures were red cell transfusion and clinical outcome. RESULTS: All preoperative data were comparable between the two groups. A significantly fewer percentage of patients in group RCV were transfused red cells (RCV = 32.6% vs. C = 53.5%, P = 0.05). No significant difference was found between any of the outcome measures with the exception of median hospital stay (RCV = 5.9 days vs. C = 6.8 days, P = 0.02). CONCLUSION: In elective cardiac surgery patients, considering haemoglobin concentration alone may overestimate the requirement for red cell transfusion. More research is required to determine the impact of restrictive transfusion policies on clinical outcome following cardiac surgery.